Fruit and two vegetables - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Fruit and vegetable production in warm climates by R P Rice, L W Rice, H D Tindall 1990 486pp ISBN 0-333-46850-3 pbk